2020
DOI: 10.1186/s13287-020-01987-y
|View full text |Cite
|
Sign up to set email alerts
|

Process data of allogeneic ex vivo-expanded ABCB5+ mesenchymal stromal cells for human use: off-the-shelf GMP-manufactured donor-independent ATMP

Abstract: Background Human dermal mesenchymal stromal cells (MSCs) expressing the ATP-binding cassette (ABC) efflux transporter ABCB5 represent an easily accessible MSC population that, based on preclinical and first-in-human data, holds significant promise to treat a broad spectrum of conditions associated not only with skin-related but also systemic inflammatory and/or degenerative processes. Methods We have developed a validated Good Manufacturing Practice-compliant expansion and manufacturing process by which ABCB5… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 27 publications
0
37
0
Order By: Relevance
“…Other markers, such as Stro-1, CD271, CD362, and ABCB5, are also considered as MSC markers by some researchers and even used for MSC flow sorting (Ning et al, 2011 ; Álvarez-Viejo et al, 2015 ; Ballikaya et al, 2020 ; Gonzalez et al, 2020 ). However, in our review we did not find these antibodies to be as available for other species or as well-demonstrated in the literature as CD29 and CD44.…”
Section: Challenges For Clinical Translation Of Mesenchymal Stromal Cmentioning
confidence: 99%
“…Other markers, such as Stro-1, CD271, CD362, and ABCB5, are also considered as MSC markers by some researchers and even used for MSC flow sorting (Ning et al, 2011 ; Álvarez-Viejo et al, 2015 ; Ballikaya et al, 2020 ; Gonzalez et al, 2020 ). However, in our review we did not find these antibodies to be as available for other species or as well-demonstrated in the literature as CD29 and CD44.…”
Section: Challenges For Clinical Translation Of Mesenchymal Stromal Cmentioning
confidence: 99%
“…4 b). Regarding the cells’ biological activity, it had to be ruled out that the fibrin gel could create a hypoxic environment that, in turn, would stimulate the LSCs to secrete proangiogenic factors such as VEGF, as is known, e.g., for ABCB5 + mesenchymal stem cells [ 31 ]. Such adaptive secretion of proangiogenic factors would facilitate angiogenesis and thus jeopardize therapeutic success.…”
Section: Discussionmentioning
confidence: 99%
“…Nuclei were counterstained with DAPI (10–12 min). For positive control, human corneal epithelial cells (Life Technologies, Darmstadt, Germany; for ΔNp63, CK3/CK12, PAX6), human skin-derived mesenchymal stem cells (TICEBA [ 31 ]; for vimentin, connexin 43) and human skin malignant melanoma cells (SK-MEL-28, ATCC® HTB-72™, LGC Standards, Wesel, Germany; for MART-1) were used. Stains were evaluated microscopically (Leica DMi8 microscope, Leica Microsystems, Wetzlar, Germany; or Floid™ cell imaging station, Life Technologies, Darmstadt, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…Human ABCB5+ DSCs (>95% ABCB5+ expression) and donor-matched ABCB5− cell fractions (<2% ABCB5+ expression) were isolated by TICEBA (Heidelberg, Germany). ABCB5+ DSCs were enriched and isolated from reticular dermis primary cell cultures of healthy skin donors as previously described, 21,22 whereas the remaining negative…”
Section: Cell Sourcementioning
confidence: 99%
“…ABCB5+ DSCs have shown promise in the field of regenerative medicine, which makes them of interest in treatment for RDEB. [20][21][22] Intradermal injections of ABCB5+ DSCs promoted healing in a chronic venous ulcer murine model, with an increase in M2 macrophages in the wound bed. 16 Our group has shown that neonatal injections of ABCB5+ DSCs in a Col7a1 −/− RDEB murine model significantly prolonged survival compared to phosphate buffered saline (PBS) control injected animals, with ABCB5+ DSC-treated mice showing decreased M1 macrophage skin infiltration.…”
Section: Introductionmentioning
confidence: 99%